CSR Untuk Cagar Budaya Surabaya (Jurnal Ilmiah Pariwisata, 2016)
Based on the study about tourism icon identification in Surabaya by Surabaya Development Planning Body in 2015, Surabaya tourism icons are cultural heritage areas that include Kota Tua, TuguPahlawan and Tunjungan Street. These tourism spots are mostly located in north Surabaya. As far as the field study is concerned, some of the buildings in those areas are still well maintained and even used for office buildings and factories. Besides that, in Kota Tua areas especially Kota TuaKolonial, some commercial buildings such as hotels and museums are still available. Unfortunately, some others are not properly preserved. They significantly affect not only the tourism destination quality but also the tourists’ special interests to visit those areas. Corporate social responsibility (CSR) is intentionally carried out to preserve cultural heritage buildings, through which the quality of heritage tourism products in Surabaya can be improved. Having used descriptive qualitative method as a research design, this study aims at describing the implementation of CSR in increasing Surabaya’s heritage tourism products. The primary data are obtained from interview and observation; meanwhile, the secondary ones are from the desk review of documents and the review of related literature. Surabaya tourism stakeholders are the key informants of the study such as the government officials, the members of legislative body, businessmen, tourists, and members of the society. This study concludes that improving the quality of Surabaya tourism icon destination is not solely the responsibility of the government. Due to vast areas of the tourism spots, firstly, the contribution of the private sectors is strongly needed to allocate the activities of CSR into different kinds of favorable actions. Second, the improvement of Surabaya’s heritage tourism product quality will affect the development of other Surabaya’s heritage products. Thirdly, some organizations or heritage area management bodies which are related to Destination Management Organization are needed in order to maintain the sustainability of those areas.